Green Synthesis of Ag-Doped CuO Nanocomposites Using Honey Solution for Evaluation of their Antimicrobial and Antioxidant Activities - Gebremichael, Tekileab Engida; Muleta, Gutta Gonfa; Tadele, Kirubel Teshome (Current Nanomaterials, 2025)
BackgroundThe rise of infectious diseases especially due to drug-resistant microbes and free radicals has caused a serious threat to public health worldwide. Green synthesized nanomaterials (NMs) have emerged as promising candidates to minimize the damage due to these problems. Doping the bioactive and stable silver atom into the biocompatible CuO by capping the nanoparticles with phytochemicals from honey enhanced the biological activity. The present study aimed to synthesize Ag- CuO NCs using the honey solution for antimicrobial and antioxidant activity evaluation.MethodsThe nanoparticles (NPs) and nanocomposites (NCs) were successfully synthesized using the honey solution and characterized by spectroscopic techniques such as XRD, UV-Vis, FTIR, and SEM. The role of the secondary metabolites in honey solution is to stabilize the fabricated NMs by capping.ResultsThe red shift observed with the addition of Ag dopant indicates the narrowing of the CuO band gap. FT-IR characterization confirmed the presence of various functional group bands in the synthesized NMs. The spectral band between 900–500 cm−1 displays the presence of metal-oxygen and metal-metal bonds, confirming the production of pure CuO NPs and Ag-CuO NCs. The fabricated CuO NPs and Ag-CuO NCs have crystalline structures with crystallite sizes of 14.14 and 17.40 nm respectively. SEM data showed that CuO NPs are spherical and Ag-CuO NCs have a mixture of spherical and cubic shapes. The NMs displayed concentration-dependent biological activities.ConclusionThe successful incorporation of silver into the crystal lattice of CuO integrated with the presence of secondary metabolites on the surface improved the potential. Hence, the prepared NMs may have pharmaceutical applications in the future with some modifications for the enhancement of their potential.
Keywords: capping